Built environment changes and active transport to school among adolescents: BEATS Natural Experiment Study protocol. Issue 3 (25th March 2020) - Mandic, Sandra; Hopkins, Debbie; García Bengoechea, Enrique; Moore, Antoni; Sandretto, Susan; Coppell, Kirsten; Ergler, Christina; Keall, Michael; Rolleston, Anna; Kidd, Gavin; Wilson, Gordon; Spence, John C
Abstract : Introduction: Natural experiments are considered a priority for examining causal associations between the built environment (BE) and physical activity (PA) because the randomised controlled trial design is rarely feasible. Few natural experiments have examined the effects of walking and cycling infrastructure on PA and active transport in adults, and none have examined the effects of such changes on PA and active transport to school among adolescents. We conducted the Built Environment and Active Transport to School (BEATS) Study in Dunedin city, New Zealand, in 2014–2017. Since 2014, on-road and off-road cycling infrastructure construction has occurred in some Dunedin neighbourhoods, including the neighbourhoods of 6 out of 12 secondary schools. Pedestrian-related infrastructure changes began in 2018. As an extension of the BEATS Study, the BEATS Natural Experiment (BEATS-NE) (2019–2022) will examine the effects of BE changes on adolescents' active transport to school in Dunedin, New Zealand. Methods and analysis: The BEATS-NE Study will employ contemporary ecological models for active transport that account for individual, social, environmental and policy factors. The published BEATS Study methodology (surveys, accelerometers, mapping, Geographic Information Science analysis and focus groups) and novel methods (environmental scan of school neighbourhoods and participatory mapping) will be used. A core component continues to be the community-based participatory approach with the sustained involvement of key stakeholders to generate locally relevant data, and facilitate knowledge translation into evidence-based policy and planning. Ethics and dissemination: The BEATS-NE Study has been approved by the University of Otago Ethics Committee (reference: 17/188). The results will be disseminated through scientific publications and symposia, and reports and presentations to stakeholders. Trial registration number: ACTRN12619001335189.